2002
DOI: 10.1002/mds.10306
|View full text |Cite
|
Sign up to set email alerts
|

Deficit of verb generation in nondemented patients with Parkinson's disease

Abstract: Clinical and neuroimaging studies have shown that verb processing suggests a preferential participation of a prefrontal network, which is dysfunctional in Parkinson's disease (PD). To assess a verb processing deficit in PD, we compared noun- and verb-generation tasks for 34 nondemented PD patients (according to the Dementia Rating Scale) with 34 matched normal subjects, using two intracategory tasks (noun/noun and verb/verb generation) and two intercategory tasks (noun/verb and verb/noun generation). PD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
99
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 38 publications
12
99
0
1
Order By: Relevance
“…This neuropsychological marker seen in our vascular MCI patients, suggesting a likely frontal lobe involvement, is consistent with the hypothesis assuming that small vessel subcortical dementia may be due to the disruption of corticostriatal loops that subserve the functions of the frontal lobes, coursing through the frontal white matter (Alexander & Crutcher, 1990;Cummings, 1993). The fact that a greater impairment in the generation of verbs than in the generation of nouns has been reported by Peran et al (2003Peran et al ( , 2004 in patients with other "subcortical" forms of dementia (Huntington's Disease and Parkinson's Disease) also supports this interpretation.…”
Section: Discussionsupporting
confidence: 91%
“…This neuropsychological marker seen in our vascular MCI patients, suggesting a likely frontal lobe involvement, is consistent with the hypothesis assuming that small vessel subcortical dementia may be due to the disruption of corticostriatal loops that subserve the functions of the frontal lobes, coursing through the frontal white matter (Alexander & Crutcher, 1990;Cummings, 1993). The fact that a greater impairment in the generation of verbs than in the generation of nouns has been reported by Peran et al (2003Peran et al ( , 2004 in patients with other "subcortical" forms of dementia (Huntington's Disease and Parkinson's Disease) also supports this interpretation.…”
Section: Discussionsupporting
confidence: 91%
“…Beilen, Leender, Post, & Bastiaanse, 2009) or a combination of both (Péran et al, 2003) is a matter of 1 debate. Decreased activation of the frontal cortex, due to reduced stimulation from the basal ganglia, is 2 considered to be the common underlying mechanism (Cotelli et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, verb fluency reflects the underlying integrity of frontal lobe circuitry, and problems on verbal fluency tasks could therefore indicate deficits in executive functioning. Péran et al (2003) developed a French word generation task that requires a semantic and grammar driven selection of single words over a limited time period. Compared to healthy control participants, non-demented PD patients made more grammatical errors in the noun-verb-generation task than in the verb-noun-generation task.…”
Section: Single Word Production Tasksmentioning
confidence: 99%
“…Compared to healthy control participants, non-demented PD patients made more grammatical errors in the noun-verb-generation task than in the verb-noun-generation task. Péran et al (2003) suggested that this discrepancy was due to the combined effect of impaired set switching and a specific grammatical impairment in verb production. The authors assume that in the verb-noun task, the impact of impaired switching is compensated by the easier noun production, whereas in the noun-verb task both the switching and production of the verb were dysfunctional.…”
Section: Single Word Production Tasksmentioning
confidence: 99%
See 1 more Smart Citation